THE RELATIONSHIP BETWEEN KNOWLEDGE AND FAMILY SUPPORT WITH PERSONAL HYGIENE IN THE ELDERLY - Nadia Sari; Miniharianti Miniharianti; Abqariah Abqariah; Wahidanur Wahidanur; Zulfa Zahra (Universitas Bina Bangsa Getsempena, 2026)
Personal hygiene disorders in the elderly are caused by the low level of support provided by the family and family knowledge. The aim of this research is to determine the relationship between family support and knowledge and personal hygiene in the elderly in Gampong Jeurat Mayang, Mutiara Timur District, Pidie Regency. This research is analytical research. The sample was all 53 elderly people using a purposive sampling technique. Data collection was carried out by distributing questionnaires. Data analysis used univariate and bivariate using Chi square. The results of the univariate test showed that the majority of elderly people's personal hygiene was poor at 31 respondents (58.5%), the majority of family support for the elderly was lacking at 27 respondents (50.9%), the majority of elderly people's family knowledge was good at 27 respondents (50.9%). ). The results of the bivariate Chi square test showed that there was a relationship between family support and personal hygiene in the elderly with a P-value of 0.000 and there was a relationship between knowledge and personal hygiene in the elderly with a P-value of 0.000. It is hoped that Puskesmas officers will provide health education on personal hygiene, as well as health problems in old age, and also provide family education to the community so that families can have the knowledge to care for the elderly.